Image quality assessment of fractures of metallic objects - Yu. I. Golub; V. V. Starovoitov (Системный анализ и прикладная информатика, 2024)
The problem of calculating a quantitative quality assessment of digital images of metal object fractures recorded by a camera or a digital microscope is considered. Quality assessment is performed when the reference images are absent. The paper presents an approach based on calculation of local estimates followed by analysis of their distribution. Several variants for calculation of local estimates have been studied. Those whose distribution is unimodal were selected. It is shown that the average of local estimates is an acceptable general characteristic of image quality if they have a normal (Gaussian) distribution. In this case, the average is one of its parameters. Otherwise, the parameters of the Weibull distribution can serve as more accurate quantitative characteristics of image quality in general. The proposed approach divides more objectively the set of the analyzed images into two groups those with satisfactory or unsatisfactory quality for performing expert studies using images. Examples of the quality assessment of different object images recorded at different resolutions are presented.